Breastfeeding and Children's Early Cognitive Outcomes - Rothstein, Donna S. (The Review of Economics and Statistics, 2013)
This paper investigates whether breastfeeding affects 5- to 6-year old children's cognitive development using three U.S. longitudinal data sets. The results for the full samples roughly point to a dose-response effect of breastfeeding on children's cognitive outcomes, with breastfeeding six months or more associated with about one-tenth of a standard deviation increase in cognitive test scores. The breastfeeding effects do not appear to be due to differences in maternal employment, cognitive ability, or parenting skills. In contrast, within-sibling results show no statistically significant breastfeeding effect.